Allergy to illicit drugs and narcotics. Issue 3 (March 2014) - Swerts, S.; Van Gasse, A.; Leysen, J.; Faber, M.; Sabato, V.; Bridts, C. H.; Jorens, P. G.; De Clerck, L. S.; Ebo, D. G.
Summary Despite their frequent use, allergy to illicit drugs and narcotics is rarely reported in literature. We present a review of the different classes of drugs of abuse that might be involved in allergies: central nervous system (CNS) depressants (such as cannabis, opioids and kava), CNS stimulants (cocaine, amphetamines, khat and ephedra) and hallucinogens such as ketamine and nutmeg. Diagnosis of drug and narcotic allergy generally relies upon careful history taking, complemented with skin testing eventually along with quantification of sIgE. However, for various reasons, correct diagnosis of most of these drug allergies is not straightforward. For example, the native plant material applied for skin testing and sIgE antibody tests might harbour irrelevant IgE‐binding structures that hamper correct diagnosis. Diagnosis might also be hampered due to uncertainties associated with the non‐specific histamine releasing characteristics of some compounds and absence of validated sIgE tests. Whether the introduction of standardized allergen components and more functional tests, that is, basophil activation and degranulation assays, might be helpful to an improved diagnosis needs to be established. It is anticipated that due to the rare character of these allergies further validation is although necessary.